Prevalence study and phylogenetic analysis of group C porcine rotavirus in the Czech Republic revealed a high level of VP6 gene heterogeneity within porcine cluster I1 - Moutelíková, Romana; Prodělalová, Jana; Dufková, Lucie (Archives of virology, 2014)
Group C rotavirus (RVC) has been described to be a causative agent of gastroenteritis in humans and animals. In the current study, the presence of porcine RVC was confirmed in 25.6 % of 293 porcine faecal samples collected from seven Czech farms. A significantly larger (p < 0.05) number of RVC-positive samples was detected in groups of finisher pigs and post-weaning piglets (4-12 weeks of age). Phylogenetic analysis of nine RVC-positive Czech strains and their comparison with available sequence data for the gene encoding RVC group antigen VP6 revealed two separate lineages within porcine cluster I1.
Keywords: Rotavirus; Animals; Female; feces; Feces; Prevalence; ženské pohlaví; Capsid Proteins; shluková analýza; lidé; Antigens, Viral; antigeny virové; prasata; Swine Diseases; Genetic Variation; Phylogeny; prevalence; Male; Rotavirus Infections; nemoci prasat; Czech Republic; Swine; virové plášťové proteiny; Česká republika; zvířata; mužské pohlaví; Cluster Analysis; fylogeneze; genetická variace; rotavirové infekce; Humans